Leggendo Fagioli che legge Bion - De Simone, Gianfranco (Il sogno della farfalla, 2024)
This article proposes some initial reflections on the analysis carried out by Massimo Fagioli on the volume by Wilfred R. Bion, Second thoughts, which appeared in the sixth chapter found in the typescript of Death instinct and knowledge, largely removed upon publication. With the aim to understand the theoretical and historical value of the text, entitled Reading W. R. Bion, it seemed crucial to analyze the historical and theoretical context of the psychoanalytic environment in which it was written. This made it possible to read this chapter as the beginning of a wider reflection on the consequences, in the psychoanalytic and psychiatric fields, of the theorization carried out by Fagioli in the previous chapters.